Nasal rhabdomyosarcoma : report of a case with immunohistochemical characterization - Cruz-Singson, Regina Patricia D.
A case of an 8-month old girl who presented with a nasal mass diagnosed as embryonal rhabdomyosarcoma, Group II-B with the use of anti-Desmin Immunostain and who underwent the current mode of management which consisted of surgery, radiation and combined chemotherapy.
Acta Medica Philippina, 1991 27 ( 1 ) pages 63-69
Keywords: Rhabdomyosarcoma; Case Reports